Hybrid Governance of Religious-Based Higher Education with Limited Autonomy and Dual Meritocracy of the University of Muhammadiyah in Indonesia - Jaenudin, Jaenudin; Victorynie, Irnie (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines how faith-based higher education institutions navigate the tension between academic autonomy and centralized ideological control within the Muhammadiyah higher education network. It employs a qualitative approach with a comparative case study design. Data consist of university statutes from four Muhammadiyah universities: Universitas Muhammadiyah Surakarta, Universitas Muhammadiyah Jakarta, Universitas Muhammadiyah Surabaya, and Universitas Pendidikan Muhammadiyah Sorong, as well as the central Internal Quality Audit (AMI) rubric. Data were collected through documentation, supported by interviews with university leaders and quality assurance units, as well as limited observations of governance practices. Data sources include both primary and secondary materials. Analysis was conducted using qualitative procedures involving data reduction, data display, and conclusion drawing. The findings reveal a hybrid governance configuration in which academic functions are decentralized to support flexibility, while strategic decision-making and resource control remain centrally coordinated. Three key dimensions emerge: constrained autonomy, dual meritocracy, and the bureaucratization of ideological values within quality assurance systems. These results indicate that institutional autonomy is structurally bounded by formalized ideological commitments. The study proposes a multi-polar governance model that integrates academic excellence with organizational identity, enabling coherence across a large and geographically dispersed higher education network.